Knowledge, attitude, and practices toward COVID-19 among the international travelers in Thailand - Suttiporn Prapaso (BMC, 2021)
Abstract Background International travel is among the leading impactful factors of COVID-19 transmission; thus, adequate knowledge, good attitude and good preventive practices toward COVID-19 for international travelers are particularly essential for successful pandemic control. Methods A cross-sectional, questionnaire-based study was conducted to determine knowledge, attitude and practices (KAP) of international travelers (both Thai and non-Thai) and expatriates in Thailand. The data were collected at the Thai Travel Clinic, Bangkok, Thailand and via online platforms during May to October 2020. The independent T-test, Chi-square test and multiple regression analysis (MRA) were applied to determine factors influencing the KAP. Results Of 399 travelers, 46.6% were male, 72.1% had a Bachelor’s degree or higher, and the mean age was 35.6 ± 9.6 years. Due to unexpected travel restrictions and lock down, 77.9% of participants were Thai and the respective major purpose of travel was business/work. Travel cancellation/postponement was reported at 73.9%. While sufficient knowledge (≥ 60% correct answers) was reported in 77.9% of participants, a low percentage of correct answers was found in the questions regarding disease transmission. The travelers reported a neutral attitude and an overall moderate concern regarding the COVID-19 situation. Adequate preventive practices were determined by the average practice score 3.54 ± 0.38 (0 = never and 4 = always). The MRA revealed that the factors influencing good practices were travelers who: i) enrolled from outside the hospital (online platform); ii) received pretravel advice at hospital; iii) were female; iv) participated before the declaration of the end of the outbreak; v) were aged 40–49 years, and vi) visited friends and relatives. Conclusions The majority of travelers in this study had sufficient knowledge, a neutral attitude and adequate preventive practices toward COVID-19. The factors influencing good practices included pretravel advice, sex, age and the point in the timeline of the outbreak. In order to better control the COVID-19 pandemic situation, pretravel counselling and advice should be promoted as a means to improve knowledge, particularly in disease transmission, increase awareness and emphasize appropriate preventive measures toward COVID-19 among international travelers. Furthermore, preventive practices should be bolstered at all times regardless of the outbreak situation.